Architecture of the fungal nuclear pore inner ring complex - Stuwe, Tobias; Fischer, Jessica; Hurt, Ed (Science, 2015)
Building a gate to the nucleus - Nuclear pore complexes form a gateway between the cytoplasm and the nucleus (see the Perspective by Ullman and Powers). Stuwe et al. combined structural, biochemical, and functional analyses to elucidate the architecture of a six-protein complex that makes up the inner ring of the fungal nuclear pore. This includes a central trimeric complex homologous to the Nup62 complex found in metazoans that is incorporated into the nuclear pore inner-ring complex. Chug et al. report the structure of the metazoan trimeric Nup62 complex. Neither study supports a model in which the pore can dilate and constrict. Instead they suggest a rigid pore in which flexible domains called FG repeats fill the channel and form a barrier that can be traversed by receptors that carry cargos across. - Science, this issue pp. 56 and 106; see also p. 33 - The nuclear pore complex (NPC) constitutes the sole gateway for bidirectional nucleocytoplasmic transport. We present the reconstitution and interdisciplinary analyses of the ~425-kilodalton inner ring complex (IRC), which forms the central transport channel and diffusion barrier of the NPC, revealing its interaction network and equimolar stoichiometry. The Nsp1•Nup49•Nup57 channel nucleoporin heterotrimer (CNT) attaches to the IRC solely through the adaptor nucleoporin Nic96. The CNT•Nic96 structure reveals that Nic96 functions as an assembly sensor that recognizes the three-dimensional architecture of the CNT, thereby mediating the incorporation of a defined CNT state into the NPC. We propose that the IRC adopts a relatively rigid scaffold that recruits the CNT to primarily form the diffusion barrier of the NPC, rather than enabling channel dilation. - A central complex in the nuclear pore forms a rigid channel filled with flexible domains that form a barrier. [Also see Perspective by Ullman and Powers] - A central complex in the nuclear pore forms a rigid channel filled with flexible domains that form a barrier. [Also see Perspective by Ullman and Powers]